Adjunctive Azithromycin Prophylaxis for Cesarean Delivery. Issue 2 (June 2017) - Tita, A.T.; Szychowski, J.M.; Boggess, K.; Saade, G.; Longo, S.; Clark, E. I; Esplin, S.; Cleary, K.; Wapner, R.; Letson, K.; Owens, M.; Abramovici, A.; et al.
Abstract : ( N Engl J Med . 2016;375(13):1231–1241) A significant cause of maternal deaths in the United States is pregnancy-associated infections postcesarean delivery. Earlier studies proposed that azithromycin-based extended spectrum antibiotic prophylaxis in combination with standard cephalosporin prophylaxis may further reduce the risk of infection following cesarean delivery compared with standard prophylaxis alone. This study aimed to evaluate whether the addition of azithromycin to standard antibiotic prophylaxis beofre skin incision would decrease the occurrence of infection postcesarean delivery without increasing the risk of other adverse maternal and perinatal outcomes.